Strategi Penyiaran Dakwah Alhikmah Radio Streaming - Siti Nur Kharisma; Ade Fadli Fachrul (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2025)
This study examines how the Da'wah broadcasting strategy is carried out by Alhikmah Radio Streaming. This study aims to determine the strategy of broadcasting Alhikmah Radio Streaming Da'wah and what are the supporting and inhibiting factors for Alhikmah Radio Streaming Da'wah broadcasting strategy. To find out the strategy of broadcasting Alhikmah Radio streaming, this study uses the theory of Fred R. David with three stages in the strategy process, namely strategy formulation, strategy implementation and strategy evaluation. This study uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation for data analysis techniques, researchers carry out data collection, data reduction, data presentation and conclusion drawing. The result of this study reveal that the broadcasting strategy of Alhikmah Radio Streaming is to focus on making the younger generation the target of their Da'wah by creating an identity or branding, discussing interesting and quality topics or themes, Utilizing Instagram as a publication medium for Alhikmah Radio activities and then evaluating for an assessment of the results carried out so that can find out the shortcomings or successes of the process and the progress that has been achieved. Factor supporting the broadcasting strategy of Alhikmah Radio Streaming Da'wah are the development of radio with a wider range, sporting facilities, and broadcaster skills that are able to package broadcast content properly. The inhibiting factor in the Alhikmah Radio Streaming Da'wah broadcasting strategy is the many options for listening to Da'wah broadcasts on other radios and other media, human resources and financial resources.